Operation 30 days at Sea: Infringements and sanctions - Comșa, Ana-Maria (Technium Social Sciences Journal, 2022)
The COVID-19 pandemic has affected every aspect of our lives and institutions, and unfortunately marine crime is also an area that has not been bypassed. Although we could say that during the lockdown period the environment was somewhat protected, it seems that after things started to return to normal and the crimes started to appear again. Between 1 and 30 March 2021, 67 states, including Romania, joined forces in a large-scale global operation coordinated by Europol and Frontex, as part of the EMPACT action plan on environmental crime, with global activities coordinated by INTERPOL. As a result of the 30 Days at Sea action, which is in its third edition, a large number of crimes against the pollution of the marine environment have been detected, and several sanctions have been applied, which proves that humanity is taking a stand against any form of environmental aggression in which we all live together. Through this article we have proposed to present and analyze both the crimes detected and the sanctions that have been applied by carrying out this extensive action, in all its three editions.